School climate and mental health among Swedish adolescents: a multilevel longitudinal study - Krisztina D. László; Filip Andersson; Maria Rosaria Galanti (BMC, 2019)
Abstract Background School is one of the most formative institutions for adolescents' development, but whether school environment affects mental health is uncertain. We investigated the association between the school's pedagogical and social climate and individual-level mental health in adolescence. Methods We studied 3416 adolescents from 94 schools involved in KUPOL, a longitudinal study conducted in eight regions in Sweden. School climate was reported by the school's teaching personnel and by the final year students using the teacher and the student versions of the Pedagogical and Social Climate Questionnaire, respectively. Index persons' mental health was assessed with the Center for Epidemiological Studies Depression Scale for Children and the Strengths and Difficulties Questionnaire. We performed multilevel logistic regression models adjusted for individual, familial and school-level confounders measured in grade 7 and exposure and outcome measured in grades 8 and 9. Results The adjusted odds ratios and 95% confidence intervals comparing the middle and the high to the lowest tertile of the total teacher school climate score were 1.47 (1.10-1.97) and 1.52 (1.11-2.09) for depressive symptoms and 1.50 (1.08-2.08) and 1.64 (1.16-2.33) for the total strengths and difficulties score. In contrast, there was no association between total student school climate score and mental health. Conclusions We found that teacher-, but not student-rated school climate was associated with an increased risk of poor mental health at the student level; the association was most pronounced for internalizing problems. Given schools' importance for adolescents' development, further studies are needed to clarify the mechanisms underlying the observed association.